Monoclonal gammopathy of clinical significance: a novel concept with therapeutic implications - Fermand, Jean-Paul; Bridoux, Frank; Dispenzieri, Angela; Jaccard, Arnaud; Kyle, Robert A.; Leung, Nelson; Merlini, Giampaolo (Blood, 2018)
Monoclonal gammopathy is a common condition, particularly in the elderly. It can indicate symptomatic multiple myeloma or another overt malignant lymphoid disorder requiring immediate chemotherapy. More frequently, it results from a small and/or quiescent secreting B-cell clone, is completely asymptomatic, and requires regular monitoring only, defining a monoclonal gammopathy of unknown significance (MGUS). Sometimes, although quiescent and not requiring any treatment per se, the clone is associated with potentially severe organ damage due to the toxicity of the monoclonal immunoglobulin or to other mechanisms. The latter situation is increasingly observed but still poorly recognized and frequently undertreated, although it often requires rapid specific intervention to preserve involved organ function. To improve early recognition and management of these small B-cell clone–related disorders, we propose to introduce the concept of monoclonal gammopathy of clinical significance (MGCS). This report identifies the spectrum of MGCSs that are classified according to mechanisms of tissue injury. It highlights the diversity of these disorders for which diagnosis and treatment are often challenging in clinical practice and require a multidisciplinary approach. Principles of management, including main diagnostic and therapeutic procedures, are also described. Importantly, efficient control of the underlying B-cell clone usually results in organ improvement. Currently, it relies mainly on chemotherapy and other anti–B-cell/plasma cell agents, which should aim at rapidly producing the best hematological response.